Anatomical and morphological characteristics of Ferula varia growing in Karaganda region (Central Kazakhstan) - Sabiyeva, А.; Smagulov, M.K.; Atazhanova, G.A.; Turdiyeva, Zh.A. (NLC “Karaganda National Research University named after аcademician Ye.A. Buketov”, 2026)
The study of plant structure makes it possible to identify characteristic features necessary for species identification and understanding of biological traits. For potentially medicinal plant raw materials, morphological and anatomical studies are an essential component of pharmacognostic analysis. The aim of this study is to investigate the structural features of the above-ground and underground organs of Ferula varia, a plant used in folk medicine, at both macro- and microscopic levels. The study was conducted on dried, crushed raw materials using staining techniques and the preparation of temporary slides. The results made it possible to describe the shape and structure of the surface of the stem and leaf plate, as well as the structural features of inflorescences and root fragments. Sparse pubescence on the stem and denser pubescence on the abaxial surface of the leaf blade were observed. At the microscopic level, the structural features and arrangement of tissues in the leaf epidermis, as well as transverse sections of the root, leaf, and stem were characterized. The obtained results made it possible to identify diagnostic features at the macro- and microscopic levels, which allows for species identification of both whole and crushed raw materials. The data obtained may be included in the draft regulatory documents for Ferula varia plant raw materials.
Қарағанды облысында (Орталық Қазақстан) өсетін Ferula varia өсімдігінің анатомиялық және морфологиялық ерекшеліктері
Анатомические и морфологические особенности Ferula varia, произрастающей в Карагандинской области (Центральный Казахстан)
Keywords: Ferula varia; above-ground and underground organs; medicinal plant raw materials; macro- and microscopy; diagnostic features